Recurrent Clostridium difficile Infection in Children: Patient Risk Factors and Markers of Intestinal Inflammation - Nicholson, Maribeth R; Crews, Jonathan D; Starke, Jeffrey R; Jiang, Zhi-Dong; DuPont, Herbert; Edwards, Kathryn (The Pediatric infectious disease journal, 2017)
The management of Clostridium difficile infection (CDI) in children is complicated by recurrence rates of 20%-30%. The identification of risk factors associated with recurrent disease might allow early recognition of those children at highest risk. Pediatric patients with CDI were identified through clinical laboratory records at 2 tertiary-care children's hospitals from March 2013 through May 2014. Subjects were enrolled and followed for 60 days to assess for recurrent CDI (rCDI). Blood samples were obtained at enrollment to evaluate host interleukin (IL)-8 polymorphisms and anti-toxin A antibody levels; stool samples were obtained for inflammatory markers (lactoferrin, calprotectin, IL-8) and C. difficile ribotype 027 strain status. Thirty days post enrollment, another serum sample was obtained to compare antibody responses. Of the 28 pediatric patients enrolled, 27 completed follow-up and 8 (30%) experienced rCDI. At enrollment, children with malignancy had significantly lower stool calprotectin, lactoferrin and IL-8 than those without malignancy. There was a trend toward increased stool inflammatory markers in those who later developed rCDI. The IL-8 A/A genotype was not associated with recurrent disease. No patients were found to have ribotype 027 or an antibody increase to toxin A. The rate of rCDI in our pediatric cohort was 30%. Children with rCDI had a trend toward higher fecal inflammatory markers with the initial infection, and these values were lower in children with malignancy. Fecal lactoferrin, calprotectin and IL-8 should be further studied to determine their value in predicting the risk of rCDI in children.